2021
DOI: 10.2298/zmspn2140059p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress on germination and seedling growth of different field pea varieties

Abstract: Germination and seedling growth of seven genotypes of field pea (Pisum sativum L.) were studied in PEG-6000 solution having osmotic potentials -0.1 and -0.2 MPa. A study was undertaken to evaluate the influence of different osmotic potentials (MPa) on seed germination percentage (GP) and mean germination time (MGT). Results show that the percentage of germination decreased with a decrease in osmotic potential, while mean germination time increased. Variety Javor is much more sensitive than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Moreover, pea seedlings were affected by drought, which was observed in shoot and root growth as well as fresh and dry biomass accumulation. These findings align with prior research on peas [47,48]. Also, it was observed that drought conditions led to a decrease in shoot and root elongation rate as well as seedling vigor index in the control.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, pea seedlings were affected by drought, which was observed in shoot and root growth as well as fresh and dry biomass accumulation. These findings align with prior research on peas [47,48]. Also, it was observed that drought conditions led to a decrease in shoot and root elongation rate as well as seedling vigor index in the control.…”
Section: Discussionsupporting
confidence: 91%
“…The aim of this research was to determine the molecular basis of osmotic stress tolerance in 7 field pea (Pisum sativum L.) varieties at the early seedling stage. A previous study of the effects of osmotic stress on germination and seedling growth of different field pea varieties (Petrović et al, 2021) showed that different concentrations of PEG in germination media significantly affect the seed germination of field pea. An increase in osmotic stress significantly decreased germination percentage (GP) in all the tested varieties.…”
Section: Enzyme Activitiesmentioning
confidence: 99%